TAMBAKNEGARA VILLAGE COMMUNITY PERCEPTION OF THE SERAYU MANGROVE ADOPTION PROGRAM - Linggarwati, Tundjung; Darmawanr, Arief Bakhtiar; Anwar, Soni Martin; Putri, Resya Nur Intan (Proceeding ICMA-SURE; Part 1 Proceeding The 8th International Conference on Multidisciplinary Approaches for Sustainable Rural Development, 2026)
The Serayu Mangrove Adoption Program is an environmental conservation initiative aimed at restoring the function of the mangrove ecosystem along the Serayu coast, particularly in Tambaknegara Village. This study aims to determine the perceptions of the Tambaknegara Village community regarding the program's implementation, as well as the extent to which the community is involved and feels its impact. The method used is a qualitative approach with data collection techniques through in-depth interviews, field observations, and documentation studies. The results show that the majority of the community has a positive perception of the mangrove adoption program, especially in terms of increasing environmental awareness, economic potential through ecotourism, and protecting riverside areas from abrasion. However, there are also several challenges such as the lack of comprehensive socialization and limited community participation in decision-making. This study concludes that the success of the mangrove adoption program is highly dependent on collaboration between the community, government, and program management institutions in creating environmental sustainability based on local participation.